Peningkatkan Aktivitas Belajar Siswa pada Pelajaran IPS melalui Penerapan Model Pembelajaran Inkuiri di Kelas V SD Negeri 091711 Pasar Baru Tahun Ajaran 2018/2019 - Alexander Samosir; Denni Saragih; Fina Panduwinata Sidabutar; Mindo Rafalaensi Sitorus (Journal on Education, 2022)
The location of this research was carried out at SD Negeri 091711 Pasar Baru which is located at Mayang Bosar Maligas, Simalungun Regency. 20 students consisting of 10 males and 10 females The method of this research is Classroom Action Research. objective test in the form of a questionnaire In cycle 1. of the 20 students who were the subjects of this study, it turned out that only 13 students (65%) already had active learning, while the remaining 7 students (35%) did not yet have active learning. the average obtained only reached 68 from the second cycle of learning activities obtained later again reduced and presented in tabular form using the same formula as cycle 1. It turns out that 17 students (85%) already have active learning, while the remaining 3 students (15%) do not yet have active learning. The average value obtained only reaches 78 The conclusion in this study is "There is an increase in student learning acuity in social studies material on patterns of economic activity through the application of inquiry learning models in class V SD Negeri 091711 Pasar Baru academic year 2018/2019"